SMALL-ANGLE NEUTRON SCATTERING AND THE MICROSTRUCTURE OF ROCKS - Radlinski A.P. (My University, 2006)
The self-similarity of rocks on the macro-scale is well known—traditionally, the photographs of rock formations usually include a scale-defining object such as a coin, a hammer, a human silhouette, etc. We know now that rock self-similarity, expressed in the quantitative language of fractal geometry, is also ubiquitous in the micro-world as well. In fact, sedimentary rocks are some of the most extensive microstructural fractal systems found in nature. Much of the knowledge of self-similarity on the micro-scale has been accumulated over the last two decades using small-angle neutron scattering (SANS) and small-angle X-ray scattering (SAXS).